2013
DOI: 10.3350/cmh.2013.19.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of telbivudine-induced myopathy in siblings with chronic hepatitis B

Abstract: Telbivudine is an L-nucleoside analogue with potent antiviral activity against hepatitis B virus (HBV). Clinical trials have shown that telbivudine has a more potent and sustained antiviral activity with a lower frequency of viral resistance than lamivudine. Although there are several reports concerning the safety profile of telbivudine, most adverse events are described as mild and transient in nature. Here we report two cases of telbivudine-induced myopathy in patients with chronic hepatitis B who were sibli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Kim et al 7 reported the telbivudine-induced myopathy of siblings, in whom muscle biopsy was not performed. The duration of telbivudine treatment in their patients was relatively shorter than our series -9 and 13 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al 7 reported the telbivudine-induced myopathy of siblings, in whom muscle biopsy was not performed. The duration of telbivudine treatment in their patients was relatively shorter than our series -9 and 13 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, previous pathological reports on telbivudine-induced myopathy did not clearly reveal the evidence of mitochondrial toxicity. 7,8 Here, we showed that the myopathy induced by prolonged use of telbivudine is a mitochondrial myopathy caused by disturbed replication of mitochondrial DNA.…”
Section: Introductionmentioning
confidence: 99%
“…42,46 Telbivudine and clevudine are comparable to entecavir in their antiviral potency but are currently not recommended owing to the frequent development of antiviral resistance and serious muscle-related problems. 42,[46][47][48][49] Entecavir and tenofovir DF have been the preferred antiviral agents for more than a decade since their approval for CHB treatment. Recently, these drugs were compared in terms of long-term treatment outcomes, especially for the prevention of HCC.…”
Section: Nasmentioning
confidence: 99%
“…For example, switching to entecavir or tenofovir DF is a reasonable option for clevudine-or telbivudine-associated myopathy. 48,49,64 Among the high genetic barrier drugs preferred as first-line agents for CHB treatment, tenofovir DF has an increased risk of renal and bone toxicity. 65 The KASL recommends substituting tenofovir DF with entecavir, tenofovir AF, or besifovir in such patients based on previous treatment history.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…There have been 20 telbivudine-induced myopathy (TIM) cases reported in the literature with detailed descriptions of clinical, imaging, or pathological features. 11 12 13 14 15 16 17 18 19 20 21 22 23 24 Two small case series included three and four patients, but for the others only a single case was reported. Little is currently known about the risk factors for this severe adverse event related to telbivudine treatment.…”
Section: Introductionmentioning
confidence: 99%